Manifestações clínicas da epidermólise bolhosa: Revisão de literatura - Angelo, Marla Monica Fagundes Cardoso; de Campos França, Diurianne Caroline [UNESP]; do Lago, Daniely Beatrice Ribeiro; Volpato, Luiz Evaristo Ricci (APESB (Associacao de Apoio a Pesquisa em Saude Bucal), 2012)
Introduction: Epidermolysis bullosa is a rare inherited skin condition characterized by the development of blisters on mucocutaneous regions of the body in response to minor traumas, heat or no apparent cause. It may manifest at birth or during the first years of life. Its classification is determined by genetics, anatomical distribution of the lesions and associated morbidity. It is divided into three main groups: epidermolysis bullosa simplex, junctional and dystrophic, covering over 30 different entities. The development of blisters in the skin and mucous membranes, and the deformities resulting from such lesions interfere excessively in the oral health, thus it is important for the dentist to know epidermolysis bullosa and to be prepared to assist patients with this condition. Objective: A comprehensive review of the literature on epidermolysis bullosa was conducted, emphasizing its clinical manifestations and the key issues that interfere with the oral health of patients suffering from the condition and with their dental care. The aim was to aid the health professionals, enabling them to provide adequate patient care, contributing to the improvement of their oral health and consequently their quality of life. Conclusion: The primary and secondary damages of epidermolysis bullosa become a real challenge for the dentist to conduct dental treatment for patients with this rare dermatosis. Before starting the treatment, it is essential to contact the health care team responsible for monitoring the patient's condition. A rehabilitating dental treatment is possible, but its conduction is very stressful, involving risks to the patient. Thus, health promotion and prevention of oral diseases should be emphasized and initiated as early as possible.
Clinical manifestations of epidermolysis bullosa: A literature review
Keywords: Comprehensive dental care; Epidermolysis bullosa; Signs and symptons